Eco home monitoring system - Aidil Amsyar, Mohd Azamee (2013)
Smart home is known among people as a luxurious set of gadgets that affordable only for elite group residence. The increase in house breaking cases trigger the need for a smart home security system for all houses. Therefore, with the rapid changing in information and communication technology (ICT), a web base system that called Economic Home Monitoring System or Eco Home Monitoring System is developed to control electrical home appliances by using Single Board Computer (SBC). By using one module of SBC that integrated by GPIO port for controlling the sensors in the electrical home devices, can tighten up the security, saving time and money. At the same time, the Eco Home Monitoring System also integrated with home camera system and home security system, which able the user to monitoring surrounding house are thru their smart smartphone, tablets, and personal computer. This Eco Home Monitoring System is user friendly, affordable and the important thing it is secure system.